Pengaruh Pembangunan Infrastruktur Terhadap Pengembangan Sektor Pertanian di Kabupaten Muaro Jambi - Fadly Elwa P; Syamsurijal Tan; Erni Achmad (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2013)
This Research aim a) To analyse infrastructure growth to, market draught irrigation Muaro Jambi Regency Period 2000-2010; b) To analyse infrastructure expense allocation growth and its proportion to totalizeing area expense Muaro Jambi Regency Period 2000-2010 c) To know and analyse ready influence infrastructure, market and irrigation to agricultural sector added value Muaro Jambi Regency Period 2000-2010. Result of research indicate that a) During period 2000-2010 infrastructure growth rate in Muaro Jambi Regency is equal to 6,60 percent per year, in same period infrastructure growth rate irrigation in Muaro Jambi Regency equal to 15,70 percent and infrastructure growth natural market growth mean equal to 18,16 percent b) meanly during period 2000-2010 infrastructure expense proportion to area expense equal to 39,85 percent, with growth per year mean equal to 65,32 percent meanly during period 2000-2010 growth agricultural sector added value Muaro Jambi Regency equal to 4,75 percent c) Infrastructure variable street, market and irrigation by together have an effect on positive and signifikan to velue added agricultural sector. By parsial infrastructure variable irrigation and street have an effect on by signifikan to agricultural sector added value, but market variable though have an effect on positive but don’t signifikan. Keywords: infrastructure , agricultural, expense